Corporate Social Responsibility Practices in Malaysian Unit Trust Industry: An Evaluation - Sawandi, Norfaiezah (International Journal of Economics and Financial Issues, 2016)
This paper aims to assess CSR initiative, particularly the voluntary education initiative, and CSR reports of two case organisations. The author applies case study approach. The case evidence is primarily constructed from three main sources, in-depth interviews, documentary review, and observation. The case organisations, FGU group, and PSU group are among the main players in Malaysian unit trust industry. Evidence suggests that PSU’s voluntary education initiative is carried out merely as public relations or as window-dressing exercise. Meanwhile, evidence suggests that there are mix drivers behind FGU’s education initiative which include social and economic factor. The study is subject to common limitations of case-based research. Although care must be exercised in interpreting the findings from the case organisations, this study does allow some tentative conclusions to be reached about CSR initiatives and reporting in the context of the Malaysian unit trust industry. Keywords: CSR initiative, CSR report, social factor, economic factor, Malaysian unit trust JEL Classifications: M49, M3